Analisis Sudut ATD pada Narapidana - Aida, Nurul; Roesma, Dewi Imelda; Tjong, Djong Hon (Jurnal Biologi UNAND, 2015)
Research on dermatoglifi and ratio 2D: 4D has been done in April to June 2013 by Stratified Random method for inmates and Random Simple (Simple Random Sampling) for non-inmates. Data processing is carried out in the Laboratory of Cytology and Genetics, Department of Biology, Faculty of Mathematics and Natural Sciences Andalas University in Padang, West Sumatra. Keywords: dermatoglifi, fingerprint patterns, inmates